Deficiency in DNA damage response of enterocytes accelerates intestinal stem cell aging in Drosophila. - Park, J.S.; Jeon, H.J.; Pyo, J.H.; Kim, Y.S.; Yoo, M.A. (Aging, 2018)
Stem cell dysfunction is closely linked to tissue and organismal aging and age-related diseases, and heavily influenced by the niche cells' environment. The DNA damage response (DDR) is a key pathway for tissue degeneration and organismal aging; however, the precise protective role of DDR in stem cell/niche aging is unclear. The Drosophila midgut is an excellent model to study the biology of stem cell/niche aging because of its easy genetic manipulation and its short lifespan. Here, we showed that deficiency of DDR in Drosophila enterocytes (ECs) accelerates intestinal stem cell (ISC) aging. We generated flies with knockdown of Mre11, Rad50, Nbs1, ATM, ATR, Chk1, and Chk2, which decrease the DDR system in ECs. EC-specific DDR depletion induced EC death, accelerated the aging of ISCs, as evidenced by ISC hyperproliferation, DNA damage accumulation, and increased centrosome amplification, and affected the adult fly's survival. Our data indicated a distinct effect of DDR depletion in stem or niche cells on tissue-resident stem cell proliferation. Our findings provide evidence of the essential role of DDR in protecting EC against ISC aging, thus providing a better understanding of the molecular mechanisms of stem cell/niche aging.